2021
DOI: 10.1007/s10661-021-08958-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring land use and soil salinity changes in coastal landscape: a case study from Senegal

Abstract: Soil salinity is a major issue causing land degradation in coastal areas. In this study, we assessed the land use and soil salinity changes in Djilor district (Senegal) using remote sensing and field data. We performed land use land cover changes for the years 1984, 1994, 2007, and 2017. Electrical conductivity was measured from 300 soil samples collected at the study area; this, together with elevation, distance to river, Normalized Difference Vegetation Index (NDVI), Salinity Index (SI), and Soil-Adjusted Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 42 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…This phenomenon was exacerbated by the national policy facilitating access to agriculture inputs for cotton farming [54]. Similar results were observed in neighboring countries, Burkina Faso [44] and Senegal [55]. We therefore advocate that any new agriculture development policy or strategy (such as cotton price incentives) should always be accompanied by an assessment of their potential environmental impacts and the design of adequate mitigation measures to ensure sustainable land use.…”
Section: Discussionmentioning
confidence: 55%
“…This phenomenon was exacerbated by the national policy facilitating access to agriculture inputs for cotton farming [54]. Similar results were observed in neighboring countries, Burkina Faso [44] and Senegal [55]. We therefore advocate that any new agriculture development policy or strategy (such as cotton price incentives) should always be accompanied by an assessment of their potential environmental impacts and the design of adequate mitigation measures to ensure sustainable land use.…”
Section: Discussionmentioning
confidence: 55%
“…Deforestation from both agricultural activity and settlement is therefore a driving factor in land cover changes [50]. Similar results were observed in neighboring countries, respectively Burkina Faso [35] and Senegal [51]. Incentives for cotton production need to be consider in land management practices for the Sahel.…”
Section: Correlation Analysismentioning
confidence: 59%
“…Wu et al [119] reported that the overall accuracy of Landsat in soil salinity detection from 1973 to 2006 was approximately 90.2%. Combining proximal instruments with remote sensing systems is advantageous in precision evaluating soil salinity [120]. Bouaziz et al [121] extracted 18 indicators from MODIS Terra data to improve salinity prediction patterns in northeastern Brazil and recognized a moderate correlation between EC and spectral indices.…”
Section: Digital Agriculture Methods and Applicationsmentioning
confidence: 99%